Evidence for Adsorption of Chlorine Species on Iron (III) (Hydr)oxides in the Sheepbed Mudstone, Gale Crater, Mars. Issue 5 (29th April 2020) - Peretyazhko, T. S.; Ralston, S. J.; Sutter, B.; Ming, D. W.
Abstract: Ancient aquatic environments in Yellowknife Bay, Gale crater, Mars, could create favorable conditions for adsorption of chlorine compounds (perchlorate and chloride) on Fe (III) (hydr)oxides present in the Sheepbed mudstone, such as akaganeite and ferrihydrite. In this work, 5.2 mM ClO4 − and 1.7 to 12 mM Cl − were adsorbed onto ferrihydrite and 5.2 mM ClO4 − was adsorbed onto akaganeite at ultraacidic (pH 2–2.5), acidic (pH 3.8–4.5), and near‐neutral (pH 6.2–7.7) pH. Samples were characterized by evolved gas analysis and compared to the data collected for the Cumberland sample from the Sheepbed mudstone. Evolved gas analysis showed that ferrihydrite with 0.5–1 wt.% ClO4 − adsorbed under ultraacidic and acidic conditions had a well‐resolved O2 peak at 306 °C due to the thermal decomposition of adsorbed ClO4 − . All akaganeite samples with 0.5 wt.% adsorbed ClO4 − had a weak peak at 312 °C tentatively assigned to decomposing perchlorate. Evolved gas analysis demonstrated that 0.5–2 wt.% Cl − adsorbed on ferrihydrite at ultraacidic and acidic pH was the main contributor to HCl evolved at >470 °C. Comparison with martian observations indicated that the temperature of the O2 peak originating from ClO4 − adsorbed on ferrihydrite matched well with the thermal evolution of O2 from the Cumberland. Evolved HCl originating from Cl − adsorbed on ferrihydrite was within the temperature range of the high‐temperature HCl release from Cumberland ( 770 °C). These observations suggest that ferrihydrite containing adsorbed ClO4 − and Cl − could exist in the mudstone. Experimental results are consistent with adsorption at acidic pH < 4 environments through postdepositional water‐rock interactions of ferrihydrite with acid‐sulfate groundwater containing dissolved chloride and perchlorate. Plain Language Summary: Chlorine species such as chloride and perchlorate are detected in Gale crater on Mars. However, the chemical nature of these species is still not well understood. We hypothesized that perchlorate and chloride could be adsorbed on Fe (III) (hydr)oxides present in Gale crater. To verify this hypothesis, we investigated adsorption on ferrihydrite and akaganeite and characterized adsorbed species with analytical techniques similar to those used on Curiosity rover. Our data indicate that adsorption of perchlorate and chloride on ferrihydrite is consistent with observations from Gale crater. These results can be used to constrain aqueous conditions on early Mars: Adsorption likely took place as a result of ferrihydrite interaction with acidic groundwater. Key Points: Ferrihydrite with adsorbed ClO4 − and Cl − could be present in the Sheepbed mudstone Thermal decomposition of adsorbed ClO4 − and Cl − may be responsible for thermally evolved O2 and HCl in the Sheepbed mudstone Adsorption likely occurred in acidic environments